Leader peptide removal in lasso peptide biosynthesis based on penultimate isoleucine residue - Duan, Yuwei; Niu, Weijing; Pang, Linlin; Mu, Da-Shuai; Du, Zong-Jun; Zhang, Youming; Bian, Xiaoying; Zhong, Guannan (Frontiers in Microbiology, 2023)
Lasso peptides are ribosomally synthesized peptides that undergo post-translational modifications including leader peptide removal by B (or the segregated B1 and B2) proteins and core peptide macrolactamization by C proteins to form a unique lariat topology. A conserved threonine residue at the penultimate position of leader peptide is hitherto found in lasso peptide precursors and shown to be a critical recognition element for effective enzymatic processing. We identified a lasso peptide biosynthetic gene cluster (bsf) from Bradymonas sediminis FA350, a Gram-negative and facultatively prey-dependent bacterium that belongs to a novel bacterial order Bradymonadales in the class Deltaproteobacteria. The kinase BsfK specifically catalyzes the phosphorylation of the precursor peptide BsfA on the Ser3 residue. BsfB1 performs dual functions to accelerate the post-translational phosphorylation and assist BsfB2 in leader peptide removal. Most importantly, the penultimate residue of leader peptide is an isoleucine rather than the conserved threonine and this isoleucine has a marked impact on the phosphorylation of Ser3 as well as leader peptide removal, implying that BsfB1 and BsfB2 exhibit a new substrate selectivity for leader peptide binding and excision. This is the first experimentally validated penultimate isoleucine residue in a lasso peptide precursor to our knowledge. In silico analysis reveals that the leader peptide Ile/Val(-2) residue is rare but not uncommon in phosphorylated lasso peptides, as this residue is also discovered in Acidobacteriaceae and Sphingomonadales in addition to Bradymonadales.